2021
DOI: 10.1186/s12916-021-02046-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of pre-pregnancy low BMI on fetal macrosomia: a population-based cohort study

Abstract: Background The differential effect of pre-pregnancy low BMI on macrosomia has not been fully addressed. Herein, we conducted a city-wide population-based cohort study to illuminate the association between pre-pregnancy low BMI and macrosomia, stratifying by maternal age, parity, and GDM status. Methods All pregnant women who paid their first prenatal visit to the hospital in Qingdao during August 1, 2018, to June 30, 2020, were recruited to this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(32 reference statements)
0
8
1
Order By: Relevance
“…An increased pre-pregnancy BMI and excessive maternal weight gain in pregnancy have been recognized as prerequisites for fetal macrosomia by many researchers [34][35][36][37]. Even a protective effect of low pre-pregnancy BMI in non-diabetic women has been described [38,39]. In our study groups, maternal pre-pregnancy obesity did not correlate with macrosomia, while excessive pregnancy weight gain correlated with large fetuses only when considering both groups and not the GDM category solely.…”
Section: Discussioncontrasting
confidence: 44%
“…An increased pre-pregnancy BMI and excessive maternal weight gain in pregnancy have been recognized as prerequisites for fetal macrosomia by many researchers [34][35][36][37]. Even a protective effect of low pre-pregnancy BMI in non-diabetic women has been described [38,39]. In our study groups, maternal pre-pregnancy obesity did not correlate with macrosomia, while excessive pregnancy weight gain correlated with large fetuses only when considering both groups and not the GDM category solely.…”
Section: Discussioncontrasting
confidence: 44%
“…( 27 ) performed a multicenter study based on 276,436 singleton livebirths or fresh stillbirths and demonstrated that higher parity was associated with a significantly increased risk of macrosomia. One possible explanation is that fetuses of nullipara were more likely to be exposed to a different maternal immune environment which might restrict the fetal growth in the uterine ( 28 ). Another possible explanation is that higher parity has been reported to be strictly related to GDM, which played an important role in the development of macrosomia ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that apart from a history of macrosomia, a higher prepregnancy BMI and gestational weight gain in the subsequent pregnancy were independent risk factors for macrosomia in multipara, which was consistent with previous studies [ 21 , 22 , 23 , 24 ]. A previous cohort study of 105,768 mother-child pairs [ 25 ] and a 10-year cross-sectional study of 84,900 participants [ 26 ] have reported that maternal low BMI was inversely associated with macrosomia. However, most of the previous studies were conducted on the European and American populations rather than the Chinese population.…”
Section: Discussionmentioning
confidence: 99%